2004
DOI: 10.1165/rcmb.2003-0330oc
|View full text |Cite
|
Sign up to set email alerts
|

The Splicing and Fate of ADAM33 Transcripts in Primary Human Airways Fibroblasts

Abstract: The ADAM (A Disintegrin and Metalloprotease) family of Zn++-dependent metalloproteases are multidomain proteins involved in diverse cellular activities. Polymorphic variation in ADAM33 is strongly associated with asthma and bronchial hyperresponsiveness. Identification of those isoforms of ADAM33 that are expressed in airways is fundamental to dissecting the role of ADAM33 in asthma. Analysis of primary human airways fibroblasts has shown the presence of a number of alternatively spliced forms of ADAM33, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
3

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 30 publications
4
60
1
3
Order By: Relevance
“…Interestingly, there is a lack of staining for the catalytic (metalloproteinase) site of ADAM19 and ADAM33, which may implicate that these ADAMs are lacking the metalloproteinase site and therefore are present in an inactive form. For ADAM33, there is suggestive evidence that this is indeed the case since alternative splice variants have been described that mostly lack the metalloproteinase site [44].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, there is a lack of staining for the catalytic (metalloproteinase) site of ADAM19 and ADAM33, which may implicate that these ADAMs are lacking the metalloproteinase site and therefore are present in an inactive form. For ADAM33, there is suggestive evidence that this is indeed the case since alternative splice variants have been described that mostly lack the metalloproteinase site [44].…”
Section: Discussionmentioning
confidence: 91%
“…Another issue of importance is that a large number of alternatively spliced forms of ADAM33 have been identified [44,45]. Some show structural similarity to a synthetic ADAM12-S that induces myogenesis [46], in turn suggesting ADAM33 to be able to induce airway smooth muscle proliferation and hypertrophy [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the metalloprotease activity of ADAM33 represents a potential target for therapeutic intervention, the only single nucleotide polymorphism that has been identified that could cause a coding change within the metalloprotease domain has a weak association with bronchial hyperresponsiveness [76]. Furthermore, POWELL et al [80] have reported that the metalloprotease domain is spliced out over 95% of transcripts in bronchial fibroblasts, suggesting that other domains of ADAM33 play important functional roles. Similarly, in bronchial biopsies, transcripts encoding the metalloprotease domain are of low abundance and there is no clear diseaserelated difference in ADAM33 expression [81].…”
Section: Increased Deposition Of Extracellular Matrixmentioning
confidence: 99%
“…ADAM33 contains >56 SNPs, of which the majority associated with asthma and BHR are found in introns controlling RNA stability and alternative splicing. In airway fibroblasts and smooth muscle, six alternatively spliced variants of ADAM33 have been discovered [79]. Under certain circumstances, a full-length ADAM33 gene can also be transported to the cell membrane where it exerts proteolytic activity [80].…”
Section: Disease Linkage Analysis and Positional Cloningmentioning
confidence: 99%